The Influence of Fintech on Financial Management Behavior: A Case Study in Sigli City, Pidie Regency - Nasruddin, Nasruddin; Darni, Surya; Wahyuni, Sri; Febriansyah, Sutan (Jurnal Akuntansi dan Keuangan, 2024)
This study aims to analyze the influence of Fintech Payment, Financial Literacy, and Service Accessibility on Financial Management among the residents of Sigli City. The research employs a quantitative approach with a survey method, involving 100 respondents selected using the Lemeshow technique. Data analysis uses Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 3.0. The findings indicate that all indicators have good validity and reliability. The evaluation of the structural model suggests that the variables of Fintech Payment, Financial Literacy, and Service Accessibility have a positive and significant impact on Financial Management. Fintech Payment assists the community in managing their finances through the features provided, Financial Literacy enhances individuals' ability to make better financial decisions, and Service Accessibility improves the ease with which the community can utilize financial services.